Cancer patterns among children of Turkish descent in Germany: A study at the German Childhood Cancer Registry - Kaatsch Peter; Zeeb Hajo; Spix Claudia; Spallek Jacob; Razum Oliver (BMC, 2008)
Abstract Background Cancer risks of migrants might differ from risks of the indigenous population due to differences in socioeconomic status, life style, or genetic factors. The aim of this study was to investigate cancer patterns among children of Turkish descent in Germany. Methods We identified cases with Turkish names (as a proxy of Turkish descent) among the 37,259 cases of childhood cancer registered in the German Childhood Cancer Registry (GCCR) during 1980-2005. As it is not possible to obtain reference population data for children of Turkish descent, the distribution of cancer diagnoses was compared between cases of Turkish descent and all remaining (mainly German) cases in the registry, using proportional cancer incidence ratios (PCIRs). Results The overall distribution of cancer diagnoses was similar in the two groups. The PCIRs in three diagnosis groups were increased for cases of Turkish descent: acute non-lymphocytic leukaemia (PCIR 1.23; CI (95%) 1.02-1.47), Hodgkin's disease (1.34; 1.13-1.59) and Non-Hodgkin/Burkitt lymphoma (1.19; 1.02-1.39). Age, sex, and period of diagnosis showed no influence on the distribution of diagnoses. Conclusion No major differences were found in cancer patterns among cases of Turkish descent compared to all other cases in the GCCR. Slightly higher proportions of systemic malignant diseases indicate that analytical studies involving migrants may help investigating the causes of such cancers.